Local Stability of Predator Prey Models With Harvesting On The Prey - Marom, Saiful (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
In this paper considered the dynamics of a predator prey model withthreshold harvesting on the prey. Theoretical and numerical methodsare used to investigate boundedness of solutions, existence ofequilibrium points, and the local stability of equilibrium points.Key words : predator prey models, boundedness of solution, localstability.